Molecular mechanisms and clinical applications of gut microbiota-derived bioactive compounds in metabolic dysfunction-associated fatty liver disease - Ma, Chengyun; Wang, Jing; Song, Xuanli; Wang, Xue; Zong, Shuai (Frontiers in Immunology, 2025)
Metabolic (dysfunction)-associated fatty liver disease (MAFLD) has emerged as a leading cause of chronic liver disease worldwide. Its pathogenesis is closely associated with gut microbiota dysbiosis and metabolic disturbances. In recent years, numerous studies have demonstrated that bioactive compounds produced by gut microbial metabolism—such as short-chain fatty acids, secondary bile acids, tryptophan derivatives, and bacterial extracellular vesicles—play critical roles in the development and progression of MAFLD by modulating hepatic lipid metabolism, inflammatory responses, and epigenetic regulation. The characteristic expression patterns of these gut microbiota-derived bioactive compounds provide novel options for differential diagnosis of the disease. Moreover, elucidation of the underlying pathological mechanisms has paved novel avenues for MAFLD treatment. Strategies including dietary interventions, prebiotics, probiotics, and other microbiota-targeted therapies are considered potential approaches to modulate MAFLD progression. This review systematically summarizes the molecular mechanisms underlying the development of MAFLD influenced by gut microbiota-derived bioactive compounds. It also explores the feasibility of utilizing specific gut microbial metabolite profiles for MAFLD diagnosis and highlights potential therapeutic strategies targeting microbiota-host metabolic interactions, including the use of engineered bacteria to produce specific metabolites, probiotic/prebiotic interventions, and the clinical prospects of fecal microbiota transplantation.